Pemberdayaan POKLAHSAR Dalam Diversifikasi Produk Teh Herbal Mangrove di Ekowisata Mangrove Denpasar: English - Putu Angga Wiradana; I Gede Widhiantara; Ni Kadek Yunita Sari; I Wayan Rosiana; Anak Agung Ayu Putri Permatasari; I Made Gde Sudyadnyana Sandhika (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2024)
Batu Lumbang Mangrove Ecotourism, located in Pemogan Village, Denpasar City, is one of the natural destinations located in a conservation area. Problems still faced by partners include not understanding the use of non-timber forest products (NTFPs) from mangroves as raw materials for food and traditional medicine and partners still need assistance to develop diversified tea bag products from mangrove leaves. Mentoring activities were carried out for 3 months at the Segara Guna Batu Lumbang Mangrove. The aim of this program is to provide education and training in making tea bags made from jeruju leaves (Acanthus ilicifolius) that are hygienic, in the right dosage, and increase partners' understanding of NTFPs through a pocket book. The method used in this community partnership program is a qualitative approach and observation. The target and output of this program is to increase partners' knowledge and skills in processing herbal drinks made from mangrove leaves and increase partners' understanding of the use of mangrove NTFPs. The results of the activity showed that there was an increase in partners' skills and knowledge of 88.87% after the program took place in processing and making herbal tea bags and utilizing mangrove pocket books.